The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5539/ijef.v10n2p28
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Macroeconomic Variables on Karachi Stock Market Returns

Abstract: The study investigated The study examines the impact of selected macroeconomic variables (inflation, exchange rate, interest rate) on Karachi stock market returns. Mainly secondary data used in the research process. The study consists of data for the period of 10 years and 5 months starting from January 2007 till May 2017. For this purpose, monthly data of KSE-100 index has been observed for the period January 2007 to May 2017. The market returns have been calculated through the opening and closing index value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
1
0
0
1
Order By: Relevance
“…Authors used regression analysis for result. The result reveals that there is significant impact on stock return and result matched with previous finding in other researcher that the inflation have negative relation with return (Pervaiz, Masih, & Jian-Zhou, 2018). Pacine (2017) empirically investigated macroeconomic factors on firm performance in the United Kingdom using data from Top 100 firm in UK during 2000 to 2014.…”
Section: Literature Reviewsupporting
confidence: 68%
“…Authors used regression analysis for result. The result reveals that there is significant impact on stock return and result matched with previous finding in other researcher that the inflation have negative relation with return (Pervaiz, Masih, & Jian-Zhou, 2018). Pacine (2017) empirically investigated macroeconomic factors on firm performance in the United Kingdom using data from Top 100 firm in UK during 2000 to 2014.…”
Section: Literature Reviewsupporting
confidence: 68%
“…Tingkat inflasi yang tinggi menunjukkan bahwa risiko investasi cukup besar sebab inflasi yang tinggi akan mengurangi rate of return dari investor. Didukung penelitian dari Iqmal & Putra (2020), Suriyani & Sudiartha (2018), Pervaiz et al (2018), dan Quandir (2012) bahwa kenaikan inflasi dapat menurunkan capital gain yang menyebabkan berkurangnya keuntungan yang diperoleh investor. Maka dapat dirumuskan hipotesis yaitu H1: Inflasi berpengaruh negatif terhadap return saham perusahaan.…”
Section: Pendahuluanunclassified
“…In their evaluation of stock prices and India's www.jrasb.com financial sector, Bhattacharya and Mukherjee (2001) discovered a negligible association between exchange rates and share market returns. Similarly, Pervaiz et al (2018) found that exchange rates and other macro factors affected Kenya's stock market returns, with the exchange rate demonstrating an unfavorable relationship with the Nairobi Stock Exchange (NSE). Recent research has indicated favorable correlations between the outcomes of the two variables in the short run, attributing this to the usual strategy, while revealing little positive correlation in the long run.…”
Section: Introductionmentioning
confidence: 99%